Characterization of Popped Sorghum (Sorghum bicolor) Based Sports Drink Premix: Unlocking Nutritional Potential - Shalini Choudhary; Karuna Singh; Muskan Chadha; Ratnakar Shukla (Engineering Proceedings, 2024)
The nutritional analyses of a sports drink premix (SDP) made with sorghum flour, Bengal gram flour, seed mix, chicory root powder and a natural flavor mix, showed 66.7 g carbohydrates, 15.8 g protein, 7.43 g fat, and 14.21 g fiber per 100 g. Mineral analysis showed that the presence of electrolytes with potassium was the highest. The total phenolic content was 77.61 mg GAE/100 g, the total DPPH was 93%/100 g of sports drink premix, and the total flavonoid content was 88%/100 g of sports drink premix. The GC-MS analysis confirmed the presence of antioxidant, antibacterial, anti-inflammatory, and anti-tubercular compounds.